Malignant triton tumor of the lung, infiltrating the left atrium and left ventricle, with metastasis to the small intestine - Tomaszewski, Dariusz; Beta, Sebastian; Rogowski, Jan A. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Malignant triton tumors are a rare subtype of malignant peripheral nerve sheath tumors showing rhabdomyosarcomatous differentiation. We report the case of a 33-year-old patient who underwent an excision of such a tumor by thoracic and cardiac surgery. He was reoperated on 1 month later because of a tumor of the small intestine and received adjuvant radiation.